IMPLEMENTASI PEMBANGUNAN INFRASTRUKTUR JALAN DESA - Mustafa .; Cahyo Sasmito (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Abstract: Implementation of road infrastructure development is the most fundamental means to support the smoothness, distribution of goods, and human transportation network. Community welfare can be seen from the condition of a physical area about the facilities provided by the government. The research method is done with the type of qualitative approach, type and source of data covering primary and secondary data. Data collection through observation techniques, interviews, and documentation. The research instruments include the researcher himself, the interview guide and the field notes. Sampling technique using purposive sampling. Validity and use triangulation techniques. Analysis by reduction, presentation and conclusion. The result of this research is 1) how the implementation of the development of village road infrastructure in Tlontoraja Village is successful and done as expected. 2) inhibiting factors and supporting the implementation of village road infrastructure development is the access to the narrow location and less good resources so that the implementation of development is less optimal then the supporting factor is given to the freedom to participate and support the financial distribution in the implementation of the development of village road infrastructure implementation of road infrastructure development and done as expected. Keywords: Implementation, Development, Infrastructure Abstrak: Implementasi pembangunan infrastruktur jalan merupakan sarana yang paling mendasar yang bertujuan untuk mendukung kelancaran, distribusi barang, maupun jaringan transportasi  manusia. Kesejahteraan masyarakat dapat dilihat dari kondisi suatu fisik daerah tentang fasilitas-fasilitas yang disediakan oleh pemerintah. Metode penelitian dilakukan dengan jenis pendekatan kualitatif, jenis dan sumber data meliputi data primer dan sekunder. Pengumpulan data melalui tehnik observasi, wawancara, dan dokumentasi. Instrumen penelitian meliputi peneliti sendiri, panduan wawancaradan catatan lapangan. Tehnik sampling menggunakan purposive sampling. Keabsahan dan menggunakan tehnik triangulasi. Analisis dengan reduksi, penyajian dan penarikan kesimpulan. Hal ini hasil dari pada penelitian adalah 1) bagaimana implementasi pembangunan infrastruktur jalan Desa di Desa Tlontoraja adalah berhasil dan terlaksana sesuai yang diharapkan. 2) faktor penghambat dan pendukung implementasi pembangunan infrastruktur jalan Desa adalah  akses ke lokasi sempit dan sumber daya kurang baik sehingga pelaksanaan pembangunan kurang optimal kemudian faktor pendukungnya adalah diberikan ke bebasan berpartisipasi dan dukungan distribusi finansial dalam pelaksanaan pembangunan infrastruktur jalan desa implementasi pembangunan infrastruktur jalan desa berhasil dan terlaksana sesuai yang diharapkan. Kata kunci: Implementasi, Pembangunan, Infrastruktur